Psychosocial Care Service in the Mental Health Provision - Tumanggor, Roxsana Devi (Caring: Indonesian Journal of Nursing Science, 2020)
The approach of health service can be divided into a medical term and psychosocial term that are applied by the mental health professional. The mental heath services help their clients with mental illness by giving a specific treatments particularly from psychological view. The information in this essay were collected from two databases that are CINAHL and Health Science.Â  It also included the University of Wollongong e-journal database for nursing program.Â  Based on the internet research, it is imperative that the intervention can be delivered in the form of case management. This paper therefore will discuss the psychosocial care for mentally ill clients in terms of concept, components, interventions and benefit in the practical area. The strategies to develop the treatment more effective are also discussed in depth. Keywords. psychosocial care, medical care, mental health.